Preoperative planning of arterial chemoembolization with drug-saturated microspheres for women with recurrent pelvic tumors complicated by bleeding - E. A. Zvezdkina; A. G. Kedrova; D. P. Lebedev; T. A. Greyan; D. N. Panchenkov; Yu. A. Stepanova (ABV-press, 2022)
Arterial chemoembolization is an X-ray surgical method that is used for recurrent pelvic tumors complicated by bleeding. It combines occlusion of tumor vessels and local chemotherapy, for which a cytostatic and drug-saturated microspheres are used. To obtain a result, two conditions must be met: carefully close all tumor afferents, treat the maximum tumor volume with saturated microspheres.The aim of the work: to define the key points of preoperative planning for recurrent pelvic tumors in women in order to achieve reliable hemostasis and cytoreduction.An analysis of 17 women with recurrent tumors complicated by tumor bleeding is presented. The first group consisted of 7 patients in whom the uterus was not removed, the second group consisted of 10 patients with removed uterus. For preoperative planning, magnetic resonance imaging of pelvis and selective angiography of the branches of the anterior and posterior trunk of the internal iliac artery were used. The sources of blood supply to the tumor were different and depended on the localization of the process in the upper, middle, and lower levels of pelvis. Multidisciplinary planning made it possible to achieve reliable hemostasis in all cases, to prevent complications from the pelvic organs.